Spiegel online - Schmedders, Karl; Rott, Armin ([London] : SAGE, 2016)
Spiegel Online (www.spiegel.de) is the leading news Web site in Germany. The site was first designed to accompany Der Spiegel, one of Europe's largest and Germany's most influential weekly magazine, which has a weekly circulation of around one million. The site's content is produced by a team of more than fifty journalists writing in several categories: politics; business; networld; panorama; arts and entertainment; science; university; school; sports; travel; weather; and automobiles. The original content is complemented by articles purchased from news agencies and selected articles from the print edition. Spiegel-Verlag is a major contributor to the Hamburg Media School, which offers professional master's degree programs in Media Management (MBA), film, and journalism. In their second year, MBA students typically engage in consulting projects with major.
Originally Published in: Schmedders, K., & Rott, A. (2008). Spiegel Online. 5-108-007. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Online journalism -- Case studies